2020
DOI: 10.1055/s-0040-1709728
|View full text |Cite
|
Sign up to set email alerts
|

How Do the Locking Screws Lock? A Micro-CT Study of 3.5-mm Locking Screw Mechanism

Abstract: Objective To quantify the amount of the screw head thread and the plate hole thread connection in two 3.5 mm locking plates: Locking Compression Plate (LCP) and Polyaxial Locking System (PLS). Materials and Methods A micro - CT scan of a screw head - plate hole connection was performed pre- and post destructive tests. Tests were performed on bone surrogates in a fracture gap model. The 3.5 LCP and 3.5 PLS plates, with 3 perpendicular screws per segment were used in a destructive static test. The 3.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…17 This finding was further supported and confirmed by a micro-CT investigation of this system. 20 By taking into consideration recently published data and our results, a 1.5 Nm torque can be recommended for the 3.5-mm PLS. Nevertheless, a further investigation of this system is required.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…17 This finding was further supported and confirmed by a micro-CT investigation of this system. 20 By taking into consideration recently published data and our results, a 1.5 Nm torque can be recommended for the 3.5-mm PLS. Nevertheless, a further investigation of this system is required.…”
Section: Discussionmentioning
confidence: 58%
“…This theory is supported by recently published data that showed that the connection regions between the screw head and the plate hole change depending on the force acting on the construct. 20 Further investigations with the use of advanced imaging pre- and post-destructive loading should be helpful in better understanding this occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…MicroCT was used to quantify the contact area between threaded parts of both the screw head and plate hole, as described by Kaczmarek et al [ 15 , 16 ]. To put it concisely, after each construct was created, it was scanned with a metrological X-ray micro-computed tomographic device (v|tome|x s240; GE Sensing & Inspection Technologies GmbH, Wunstorf, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Following the method developed by Kaczmarek et al X-ray microcomputed tomography was utilized to measure the contact area between the threaded portions of the screw head and the plate hole 25 , 26 . Each construct was scanned using a metrological computed tomographic device (v|tome|x s240; GE Sensing & Inspection Technologies GmbH, Wunstorf, Germany).…”
Section: Methodsmentioning
confidence: 99%